Preparation of Cryogenik Alcohol - Erika Yusnidar Samosir (Universitas Negeri Medan, 2022)
Cryonics is an effort to preserve the human body in frozen conditions with the aim of reviving it at some time in the future. Cryogenic techniques have been developed to increase the solubility of a drug by creating amorphous drug particles with a nanoparticle structure and have high porosity under very low temperature conditions. So that a dry powder is formed which can be obtained from a drying process such as freeze drying. Cryogenic freezing is usually carried out using the help of a liquefied gas such as helium. In the medical field, cryogenic freezing is used to preserve vaccines so that they remain stable and can be stored for a long time. After freezing at low temperatures, these various items can be kept frozen by means of special refrigeration units, including mobile freezer units, thus making shipping possible.